Fire fighting robot with vision camera and gas sensors - Boopalan, S; Narendra Prasad, G; Swaraj Paul, C; Narayanan, Kumar; Anandan, R (International Journal of Engineering and Technology, 2018)
Yearly there are 150+ deaths are occurring due to fire fighting operations. Most of the deaths are due to presence of poisonous gases being present in the fire fighting areas. If we able to inform fire fighter worker about the presence of gases and hazardous situation, we can able to save their lives.Â In now-a-daysÂ robots play a vital part in industry and normal life of human beings , robotsÂ areÂ the assembleÂ Â ofÂ different parts or things which are made by human in order to complete any work with more accuracy.Â â€œFire Fighting Robot with gas sensorsâ€. The design is costless and will do lot of work. It can be used in industry and for domestic purpose. Important parts involved in the construction of robot are gas sensors, water tank, wireless remote and wireless android device Wi-Fi enabled Camera, A wireless robot will do effective work, thereby making it possible to control the robot from remote location. Keeping all above factors in mind the Robot is capable of being remotely controlled and live video buffering i.e. possessing a multimedia interface was convinced and developed.Â Â